Sistem Pencahayaan pada Kantor Sequislife di Gedung Intiland Tower Surabaya - Hedy C. Indrani, Ponco Kusumo Oetomo (Intra, 2013)
Officeâs lighting is one of important aspect that can improve residentsâ performance. Sequislife Office is located in Intiland Tower building where this building is one of the eco-friendly architecture and it designed to be a building that cares for the physical and mental health of its residents. However, at this office, the artificial lighting is more dominant than the natural lighting, where this thing is not supported the Green Building concept of Intiland Tower building itself, and the artificial lighting in this building is also not conformed the standard. Through the quantitative research methods, the effectiveness systems research and its application to the office lighting is based on the concept of Sequislife environmentally friendly, and the acquisition of light intensity will be compared with the Indonesian National Standard. Optimizing light through a simulation program is one of the ways in which to obtain the appropriate light intensity of existing standards and expected to maximize the performance of future occupants of the office.